Perancangan Taman Sampangan sebagai Zona Aktivitas Gratis dengan Pendekatan Placemaking yang Mengintegrasikan Ekonomi Informal dalam Ruang Publik - Nadya Fatkhey Jannah; Wakhidah Kurniawati; Johanes Adi Nugroho (Jurnal Riptek, 2026)
This study presents a redesign of Sampangan Park (Semarang) into a Free Activity Zone intended to support community socio-economic and social interaction activities. Adopting the LIFE framework (Local Economy Activation, Inclusive Social Interaction, Free Public Access, Eco-friendly), the research uses a case-study approach combining primary (field observation, questionnaires, informal interviews) and secondary data (planning documents and literature). Data were analysed through site analysis, activity analysis, and SWOT to identify strategic issues, followed by spatial zoning and 3-D visualization to formulate design responses. Findings show that Sampangan Park has strategic locational advantages (proximity to arterial roads and existing street vendors) and a multifunctional amphitheatre that can catalyse diverse community activities; however, constraints include pedestrian obstruction by informal vendors, inadequate lighting, drainage and uneven maintenance. The proposed design reintroduces integrated seating, a designated PKL (street vendor) corridor, a history plaza, improved signage and inclusive access (disability-friendly circulation), while preserving green elements and improving management provisions. The study concludes that a zoning + participatory management approach can strengthen the park’s role as an accessible socio-economic public space and recommends further participatory monitoring and a governance plan for implementation.